Epizootics and natural enemy complex associated with palm white grubs Leucopholis spp. in South India - Prathibha, P. S.; Sajan, Jilu V.; Josephrajkumar, A.; Shyama Prasad, K. (Journal of Plantation Crops, 2026)
Leucopholis spp. white grubs are subterranean polyphagous pests of palms in the southern and north-eastern regions of India. Natural enemies play a vital role in effectively suppressing and regulating pest populations, thereby maintaining ecological balance in a sustainable manner. A terrestrial crab was observed predating on arecanut white grub, Leucopholis lepidophora in Karnataka. Natural parasitism(1.66%) by the ecto-solitary larval parasitoid Campsomeriella collaris collaris Fabricius (Hymenoptera: Scoliidae) was recorded on coconut white grubs, L. coneophora in organic gardens of Kerala. Additionally, a solitary endo-larval parasitoid, Prosena sp. nr. siberita (Diptera:Tachinidae), was documented for the first time on L. coneophora with 0.83% natural parasitism. Amber disease(2.34%) caused by Serratia spp. on L. coneophora and L. burmeisteri, mortality of second instar grub within 10–12 days of exposure under laboratory assay was also observed. White muscardine fungus (Beauveria brongniartii) was isolated and Koch’s postulates were established on early instar larvae of L. coneophora. Additionally, green muscardine disease (0.18% incidence) due to Metarhizium anisopliae and natural infection of (3.93%) of caterpillar fungus (Cordyceps spp.) were observed on third instar larvae of L coneophora. Entomopathogenic nematodes Steinernema sp. showed higher pathogenicity (LT₅₀=5.104 days at 8000 IJs) compared to Heterorhabditis indica (LT₅₀=14.576 days at 8073 IJs). Despite the identification of diverse natural pathogens associated with white grub populations, their practical exploitation as biological control agent remains limited due to inconsistent performance under natural conditions. Thus, only entomopathogenic nematodes have emerged as promising candidates for effective biocontrol.